2007
DOI: 10.3938/jkps.51.1663
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Chip LED Sensor Module at 770 nm for Fat Thickness Measurement of Optical Tissue Phantoms and Human Body Tissue

Abstract: We measured the fat thickness noninvasively by using a diffuse optical method for tissuesimulating phantoms and human tissues. A light source module composed of 770 nm low-power chip LEDs and a photo-detector were used in this study. The optical tissue phantoms were composed of a fat and a muscle layer made with gels with appropriate absorption/scattering coefficients. The fat thickness was varied from several to 30 mm. After a proper calibration procedure, we used this system to conduct human studies. Based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Accordingly, the surface structure and tissue composition can be noninvasively accessed by light [ 14 ]. Optoelectronic systems can obtain backscattered light signals, captured on a photo-detector, and estimate skin fat thickness measurements [ 15 ]. Certain wavelengths of the electromagnetic spectrum have the potential to contribute to the prediction of skin thickness and other skin properties.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the surface structure and tissue composition can be noninvasively accessed by light [ 14 ]. Optoelectronic systems can obtain backscattered light signals, captured on a photo-detector, and estimate skin fat thickness measurements [ 15 ]. Certain wavelengths of the electromagnetic spectrum have the potential to contribute to the prediction of skin thickness and other skin properties.…”
Section: Introductionmentioning
confidence: 99%
“…As the SD distance becomes larger, there exists a higher probability that some portion of the photons will reach the fat-muscle interface. In our previous study, we showed that when the SD is about 20 mm, a fat thickness of up to 20 mm will significantly affect the diffuse reflectance intensity [7]. Fig.…”
Section: Theorymentioning
confidence: 99%
“…In our previous study, we constructed a sensor module with a packaged chip LED at a 770 nm wavelength and tested its performance using two layer tissue phantoms [7][8].…”
Section: Introductionmentioning
confidence: 99%